[BOOK REVIEW] Menuju Fiqh Keluarga Progresif - Yulianti, Rahmani Timorita (Al-Mawarid Jurnal Hukum Islam, 2015)
Discourse of Muslim family issues from the classical period to the contemporary era today, has undergone with dynamics need to be responsive justification of Islamic law. The dynamics of family issues can not be separated from the changes taking place in society. According to James W. Vand er Zanden in Nasruddin Rusli1 that happened changes were caused by several factors, for instances a) Increasing or decreasing the population and changes in the ecosystem that exists around humans. b) Other Effect of cultural community as a result of cultural interaction. c) The nature of the community collectively, movement, and social revolution. and d) Tech- and modernity.